Predictive parameters of arteriovenous fistula maturation in patients with end-stage renal disease - Muhammad A. Siddiqui; Suhel Ashraff; Derek Santos; Robert Rush; Thomas Carline; Zahid Raza (The Korean Society of Nephrology, 2018)
Background: The objevctive of the present study was to explore the potential influence of blood markers and patient factors such as risk factors, kidney function profile, coagulation profile, lipid profile, body mass index, blood pressure, and vein diameter on the maturation of arteriovenous fistula (AVF) in patients with end-stage renal disease. Methods: Retrospective data from 300 patients who had undergone AVF creation at the Royal Infirmary of Edinburgh were examined. A predictive logistic regression model was developed using a backward stepwise procedure. Model performance, discrimination, and calibration were assessed using the receiver operating characteristic (ROC) curve and Hosmer-Lemeshow goodness-of-fit test. The final model was externally validated by 100 prospective patients who received a new fistula at the Royal Infirmary of Edinburgh. Results: A total of 400 (300 retrospective and 100 prospective) patients were recruited for this study, with a mean age of 60.14 ± 15.9 years (development set) and 58 ± 15 years (validation set), respectively (P = 0.208). Study results showed that males were twice as likely to undergo fistula maturation as females, while patients with no evidence of peripheral vascular disease (PVD) were three times more likely to mature their fistula and a preoperative vein diameter > 2.5 mm resulted in a fivefold increase in fistula maturation as compared with a vein size of less than 2.5 mm. The model for fistula maturation had fair discrimination, as indicated by the area under the ROC curve (0.68), but good calibration as indicated by the Hosmer-Lemeshow test (P = 0.79). The area under the receiver operating curve for the validation model in the validation set was 0.59. Similarly, in the validation set, the Hosmer-Lemeshow statistic indicated an agreement between the observed and predicted probabilities of maturation (P⟩ 0.05). Conclusion: Gender, PVD, and vein size are independent predictors of AVF maturation. The clinical utility of these risk categories in the maturation of AVF requires further evaluation in longer follow-up.